MODELING THE USE OF WORKING CAPITAL IN ORDER TO ENSURE STABILIZATION OF THE REPRODUCTION PROCESS IN AGRICULTURE - Natalya BONDINA; Igor BONDIN; Olga LAVRINA; Tatyana ZUBKOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article deals with the effective use of working capital in reproductive process of agriculture and in ensuring its sustainable development, which ensures the growth of the final product production, the improvement of its quality, cost reduction and, as a consequence, increases profits. Entire and timely provision of agricultural commodity producers with material resources and their effective use are necessary conditions for maintaining the production process and increasing its efficiency. However, in reality, the reproduction of the main types of material resources is violated and carried out on a "narrowed" basis. In order to stabilize the reproductive process in agriculture, the authors suggest a model for the efficient use of working capital in agricultural production, based on the use of a multi-stage algorithm that implements an integrated approach to determining the level of efficiency of working capital use in specific conditions.